Manufacturing Driving Circular Economy Proceedings of the 18th Global Conference on Sustainable Manufacturing, October 5-7, 2022, Berlin - Kohl, Holger; Seliger, Günther; Dietrich, Franz (Lecture Notes in Mechanical Engineering, 2023)
This is an open access book. It gathers the proceedings of the 18th Global Conference on Sustainable Manufacturing, held on October 5-7, 2022, as a hybrid event, in/from Berlin, Germany. With a focus on manufacturing advances and practices driving the circular economy, the chapters selected for this book report on sustainable manufacturing technologies for the mobility, energy and construction sector, and for machines and equipments, covering applications of artificial intelligence and industry 4.0. Moreover, they discuss energy-efficient process, waste reuse, and CO2 neutral production, giving a special emphasis to developing sustainable manufacturing in emerging countries. This book offers extensive and timely information for both researchers and professionals in the field of manufacturing and business development.